Mengungkap Faktor-Faktor Penghambat Kemampuan Menulis Siswa Kelas 2 Madrasah Ibtidaiyah Birul Walidain Widodaren - Kusna, Kufita Riska; Septianingrum, Kartika; Chaeroh, Miratu (LP. Ma'arif Janggan Magetan, 2024)
This study aims to identify factors that inhibit writing skills in grade 2 students of Madrasah Ibtidaiyah (MI) Birul Walidain in Widodaren. The research methods used included classroom observation, interviews with teachers, and student surveys, with the participation of 6 grade 2 students of MI Birul Walidain Widodaren. Data analysis using milles and huberman techniques. The results showed several significant factors that hindered students' writing skills. The main obstacle in learning to write is the lack of focus and practice at home, where parents focus more on reading skills. The importance of providing time and opportunities for students to practice writing each day is highlighted as an important strategy in improving students' writing skills. The implication of this research is the need to develop strategies to improve student focus, increase parents' awareness of the importance of learning to write at home, and provide students with time and opportunities to practice writing every day.